The retrospective economic vulnerability index, 2015 update - Sosso Feindouno; Michaël Goujon (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
This document presents detailed calculation principles for annual retrospective series of the Economic Vulnerability Index according to the UN-CDP definitions of the 2015 Review. It is organized as successive technical sheets explaining calculation of the retrospective EVI components and presenting adjustments that had to be made to obtain retrospective series. Retrospective series cover 145 developing countries (among which 48 LDCs and 97 non-LDCs) over the 1990-2013 period (starting in 1975 for some components and countries). These series are gathered in the companion database which is publicly available on the Ferdi's website. An associated website allows users to build their own EVI from these retrospective series (http://byind.ferdi.fr/).
Keywords: 330